PERANAN PAJAK DAN SEIGNIORAGE TERHADAP KETAHANAN FISKAL - Tahwin, Muhammad (potensio, 2008)
Success of the economic development is influenced by fiscaland monetary management with their regulations. Fiscal roleis carried out in two basic corridors, fiscal consolidationwhich is carried out by controlling budget deficit, and strategyof budget funding which is intended to decrease the burdenand risk of the government debt. This fact shows that fiscaland monetary policies in Indonesia is not carried out in agood harmony and synchronization. So, increasing of fiscaland monetary policies coordination is needed bysynchronizing policies goal to stabilize monetary sectors.The source of government income which derives from taxor seigniorage has important role to increase fiscalendurance. So, it is important for the government tosynchronize fiscal and monetary policies by equalizing theincreasing of tax and price level.Key Words : Tax, Seigniorage